Fact-checking of timetabling principles: a case study on the relationship between planned headways and delays - Cerreto, Fabrizio; Jonasson, Megan Holt (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
The tradeoff between reliability and level of service is a central focus for railway operators and infrastructure managers. A well-performing timetable must include an optimal level of buffer time between conflicting train movements, such that a high service delivery and a high service quality are maintained. This focus on buffer time has informed the research within the fields of timetable optimization, capacity utilization and delay propagation modeling. Despite recent and ongoing advancements in these fields, there are still disconnects between the theoretical models and their application in the design, planning and evaluation of railway timetabling. Parameters that are used in timetabling, as well as, as input to the analytical assessment models, are typically derived from practical experience and based on the macroscopic limitations of a system, rather than the microscopic conflicts inherent in its signaling system. The objective of this paper is to support the design of fact-based timetables by introducing a method of applying statistical analysis of the relationship between planned headways and recorded delays to estimate the minimum feasible headway between conflicting train movements in a railway system. This method is applied on the busiest railway line in Denmark and the results from recorded operations are validated through microsimulation.